2014
DOI: 10.1103/physrevlett.113.202301
|View full text |Cite
|
Sign up to set email alerts
|

New Exact Solution of the Relativistic Boltzmann Equation and its Hydrodynamic Limit

Abstract: We present an exact solution of the relativistic Boltzmann equation for a system undergoing boost-invariant longitudinal and azimuthally symmetric transverse flow ("Gubser flow"). The resulting exact non-equilibrium dynamics is compared to 1st-and 2nd-order relativistic hydrodynamic approximations for various shear viscosity to entropy density ratios. This novel solution can be used to test the validity and accuracy of different hydrodynamic approximations in conditions similar to those generated in relativist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
229
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 148 publications
(233 citation statements)
references
References 42 publications
4
229
0
Order By: Relevance
“…The four-vector z µ is orthogonal to u µ and in the LRF points in the longitudinal direction (identified with the direction of the dynamicallyevolving anisotropy in the system,n) [40]. 6 This assumption has been tested elsewhere by comparing the predictions of anisotropic hydrodynamics to exact solutions of the Boltzmann equation in a variety of special cases [42][43][44][45][46][47][48][49]. 7 We assume vanishing chemical potential gradients.…”
Section: (3+1)d Anisotropic Hydrodynamicsmentioning
confidence: 99%
“…The four-vector z µ is orthogonal to u µ and in the LRF points in the longitudinal direction (identified with the direction of the dynamicallyevolving anisotropy in the system,n) [40]. 6 This assumption has been tested elsewhere by comparing the predictions of anisotropic hydrodynamics to exact solutions of the Boltzmann equation in a variety of special cases [42][43][44][45][46][47][48][49]. 7 We assume vanishing chemical potential gradients.…”
Section: (3+1)d Anisotropic Hydrodynamicsmentioning
confidence: 99%
“…One way to achieve this task is to compare the results of various hydrodynamic approaches [2][3][4][5][6][7][8][9][10][11][12], which differ by the number of terms included in the formalism and by the values of the transport coefficients, with the results of the underlying microscopic kinetic theory [13][14][15][16][17][18]. The latter is very often used as a staring point to derive the specific form of the evolution equations of relativistic hydrodynamics, however, several approximations done in such procedures may result in differences between the predictions of the kinetic theory and the hydrodynamic models constructed directly with its help.…”
Section: Introductionmentioning
confidence: 99%
“…Since the two original papers [33,34], there has been a great deal of progress in aHydro [35][36][37][38][39][40][41][42][43][44][45][46] including applications to cold atomic gases near the unitary limit [47,48]. In parallel, there have been efforts to construct exact solutions to the Boltzmann equation in some simple cases which can be used to test the efficacy of various dissipative hydrodynamics approaches, and it has been shown that aHydro most accurately reproduces all known exact solutions, even in the limit of very large η/s and/or initial momentum-space anisotropy [45,[49][50][51][52][53][54].A recent focus of research has been on turning aHydro into a practical phenomenological tool with a realistic equation of state (EoS) and self-consistent anisotropic hadronic freeze-out. In this paper, we present the first comparisons of experimental data with phenomenological results obtained using (1) generalized 3+1d aHydro including three momentum-space anisotropy parameters in the underlying distribution function, (2) the quasiparticle aHydro (aHydroQP) method for implementing a realistic EoS [43,46,55] and (3) anisotropic Cooper-Frye freezeout [46,56] using the same distribution form as was assumed for the dynamical equations.…”
mentioning
confidence: 99%